How health literacy relates to venous leg ulcer healing: A scoping review. - Ayoub Bouguettaya; Georgina Gethin; Sebastian Probst; Jane Sixsmith; Victoria Team; Carolina Weller (PLoS ONE)
Background The level of personal health literacy of patients with venous leg ulcers is likely to affect their ability to self-manage their condition impacting on their adherence to treatment and influences healing and recovery outcomes. Objectives To scope existing research that examined the level of health literacy in venous leg ulcer patients, to identify how this may link to self-management behaviours (particularly physical activity and compression adherence), and venous leg ulcer healing outcomes. Methods This scoping review was based on the PRISMA-ScR six-stage framework. We searched MEDLINE, EMBASE, the Cochrane Library, PsycInfo and Health, Open Grey, and Google Scholar for publications examining general and specific health literacy in those with venous leg ulcers and for those examining any potential links of health literacy with self-management/healing generally, published between 2000-2020. This search was guided by a published protocol; studies that described other types of ulcers or did not examine health literacy were excluded. After applying inclusion and exclusion criteria the initial search identified 660 articles. Results We included five articles. Four studies used randomised controlled trials or experimental designs to test the effect of specific health literacy interventions on venous leg ulcer knowledge, compression therapy use, or healing outcomes. One study was a cross- sectional survey with qualitative elements, assessing health literacy in venous leg ulcer patients. Broadly, the research suggested that health literacy was suboptimal amongst those with venous leg ulcers, and health literacy interventions had limited effects on improving key venous leg ulcer specific outcomes. Conclusion This review provides a synthesis of extant literature examining health literacy in patients with venous leg ulcers. We identified a dearth of literature investigating the value of general and specific health literacy interventions in this space. Most importantly, no recent research on general health literacy and venous leg ulcers was identified, despite strong theoretical utility to do so. The few studies identified largely indicated that targeting health literacy of patients with venous leg ulcers is a viable area of research and intervention, encouraging future researchers and clinicians to consider patient health literacy in venous leg ulcer management.